Development of problem-based learning worksheets combined with the make a match cooperative model to enhance students' critical thinking skills in biology - Tambunan, Sari Putri Ramadani; Khairuna, Khairuna (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to (1) produce Problem Based Learning-based Learning Worksheets combined with Make A Match which is feasible to use based on expert judgment assessment (2) to determine the effectiveness of Problem Based Learning-based Learning Worksheets combined with Make A Match and (3) to determine the practicality of Problem Based Learning-based Learning Worksheets in training students' critical thinking skills in the biology subject X-MIA virus material at MA Laboratorium Uinsu. This research is a development research with the 4-D model which consists of four stages, namely, define (defining), design (planning), develope (development), and disseminate (dissemination). Data collection was obtained through product feasibility validation results, student and teacher responses, as well as pretest and posttest with N-Gain analysis. The results showed that: (1) Problem Based Learning Learning Worksheets combined with Make A Match to train critical thinking skills is declared feasible to be used by students as learning media with a 99% media validation score, 91% material validation score. (2) The effectiveness of Problem Based Learning Learning Worksheets combined with Make A Match in training students' critical thinking skills based on the results of the N-Gain analysis obtained a result of 0.7 with a high critical thinking level category with the criteria